Facies characteristics and depositional setting of the miocene Tajau member (KUDAT Formation): A sand-dominated submarine fan system / Hafzan Eva Mansor - Hafzan Eva , Mansor (2021)
There have been many disagreements regarding the stratigraphy and depositional setting of the Miocene Tajau Member of the Kudat Formation, northern Sabah, Malaysia. This work describes and discusses the stratigraphy and facies characteristics of the unit. Forty (40) sections, covering a total thickness of 2 288 m, were logged in order to conduct a detailed facies and bed type analysis of the Tajau Member. Twelve (12) facies have been identified, interpreted as the deposits of subaqueous sediment density flows, which are common processes in deep marine depositional settings. These include debrites, hyperconcentrated density flow deposits and turbidites. Several of the turbidite facies display evidence for hydraulic jumps, which are also common processes in deepwater settings and probably indicate changes in slope topography or loss of flow confinement. Facies previously identified by previous workers as hummocky cross-stratification in the Tajau Member, which was used to support a shallow marine interpretation, is better interpreted as supercritical antidunes developed in high-density turbidites, based on the coarse-grained texture, spaced layering and association with other subaqueous density flow deposits. Trace fossils characteristic of the Nereites ichnofossils are also diagnostic of a deep marine depositional environment. Eight bed types are recognized in the Tajau Member: i) tripartite beds with a debrite (BT 1) interpreted as hybrid event beds recording downslope flow transformation between turbulent and laminar states; ii) Beds showing a mixture of depositional, erosional and bypass features (BT 2, BT 4, BT 5) interpreted as recording transitions between supercritical and subcritical flow conditions triggered by hydraulic jumps; iii) bipartite beds with a basal massive sandstone overlain by fine-grained facies (BT 3) interpreted as hyperconcentrated flow with evidence of down-current flow transformation; iv) bipartite beds with a basal high-density turbidite overlain by a low-density turbidite and separated by a grain-size break (BT 6) interpreted as deposition of turbidity current with evidence of flow bypass; v) basal tractive structures capped by fine-grained facies as the product of reworking of very coarse- to coarse-grained sediments caused by lateral spreading of turbulence flow; and vi) Bouma Tbcde sequences (BT 8) interpreted as the deposits of high-to-low-density turbidity currents. The bed types reflect down-current evolution of bipartite turbulent flows, with associated transformation into co-genetic debris flows. The facies and bed type analysis has enabled the construction of a depositional model for the Tajau Member which consists of: 1) a proximal depositional zone in the centre of the study area, which was dominated by hydraulic jumps and sediment bypass of turbidity current, which represents a channel-lobe transition zone (CLTZs/BTA 1); and 2) a distal depositional zone in the north-and-south of the study area, dominated by tabular, sheet-like elements bioturbated with the Nereites ichnofossil, of depositional lobe sub-environments (i.e. lobe-axis/BTA 2, lobe-off axis/BTA 3, frontal lobe fringe/BTA 4, and distal lobe fringe/BTA 5).